IPTEKS MENGUKUR NILAI PERUSAHAAN DI PASAR MODAL PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sondakh, Renly; Morasa, Jenny (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2019)
Investment is an investment activity to obtain a return on investment (return) that will be received in the future. In investing, investors should see whether the company that will buy the shares is good or not, so investors should analyze or measure the value of the company to buy shares by using price earnings ratio and price to book value so that investors know which company is good not. Through this research, it is explained how to measure the value of the company that will be bought in its shares. This study also aims to find out how to measure the value of the company to be purchased.